Electrocaloric devices part II: All-solid heat pump without moving parts - Farrukh Najmi (Journal of Advanced Dielectrics, 2020)
Various designs have been introduced to build heat pumps using the electrocaloric effect (ECE). Each of all the current designs uses at least one moving part, which significantly reduces the reliability of the pump and adds complexities. In this work, a new all-solid design is introduced, in which two layers of an electrocaloric material (ECM) are permanently sandwiched in the source and sink, which would significantly increase the device’s reliability since nothing moves and all are permanently bound together. More importantly, the electric fields applied on two ECM layers are independently controlled. A special sequence for the electric fields on two ECM layers is introduced. Numerical calculation was used to simulate the device’s performance by using the newly introduced analytical solutions for the heat conduction in the system. It is concluded that a continuous heat transformation from the source to sink at the same temperature can be achieved when the contacting coefficient, Kε=(kcρccpc)∕(koρocpo), is very small, where k, ρ, and cp are thermal conductivity, density, and heat capacity, respectively, while the superscript c and o represent the ECM and source/sink, respectively.